Scientific-theoretical foundations of the use of ict in ensuring management efficiency and security in enterprises - Khalilov , Bekzod (GREEN ECONOMY AND DEVELOPMENT, 2025)
This article theoretically analyzes the role and significance of information and communication technologies (ICT) in ensuring management efficiency and security in enterprises. It substantiates the possibilities of forming effective and sustainable management through digital management platforms, cross-border applications, and ecological digital solutions.